2014
DOI: 10.3390/en7117640
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristic Algorithms Applied to Bioenergy Supply Chain Problems: Theory, Review, Challenges, and Future

Abstract: Bioenergy is a new source of energy that accounts for a substantial portion of the renewable energy production in many countries. The production of bioenergy is expected to increase due to its unique advantages, such as no harmful emissions and abundance. Supply-related problems are the main obstacles precluding the increase of use of biomass (which is bulky and has low energy density) to produce bioenergy. To overcome this challenge, large-scale optimization models are needed to be solved to enable decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Swarm intelligence has different algorithms, such as particle swarm optimization (PSO) and ant colony optimization (ACO; Chakraborty & Kar, 2017). Previous studies have demonstrated the powerful capability of using heuristics to find near‐optimal solutions for complex problems such as BSC planning and scheduling (Castillo‐Villar, 2014; Devika et al, 2014; Keller, 2018).…”
Section: Artificial Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Swarm intelligence has different algorithms, such as particle swarm optimization (PSO) and ant colony optimization (ACO; Chakraborty & Kar, 2017). Previous studies have demonstrated the powerful capability of using heuristics to find near‐optimal solutions for complex problems such as BSC planning and scheduling (Castillo‐Villar, 2014; Devika et al, 2014; Keller, 2018).…”
Section: Artificial Intelligencementioning
confidence: 99%
“…However, previous studies indicated the tremendous potential of AI in addressing barriers in bioenergy development. For example, Castillo‐Villar reviewed 51 case studies using metaheuristic algorithms to address the bioenergy supply chain (BSC) challenges (Castillo‐Villar, 2014). Ardabili et al reviewed the applications of machine learning and deep learning techniques in various biofuel research domains (Ardabili et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mathematical methods include linear programming (LP), non-linear programming, mixed integer linear programming NLP, MILP, goal programming (GP), compromise programming CP, and dynamic programming [24]. Heuristic methods include ones such as simulating annealing (SA), genetic algorithm (GA), non-dominated sorting genetic algorithm (NSGA), and tabu search TS [25][26][27] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In that work, insights on carbon regulatory mechanisms and other uncertainties observed in biofuel supply chains was provided. A holistic review on metaheuristic techniques implemented to bioenergy supply chains could be seen in De Meyer et al [20] and Castillo-Villar [14].…”
Section: Introductionmentioning
confidence: 99%